Intelligence: human, economic and artificial against the effects of Covid-19 (Dimensión Empresarial, 2020)
The current health crisis has led to an international economic crisis that has caused great social uncertainty that puts national governments in check. The Covid-19 places an enormous burden on health systems that poses a social and political challenge leading to a call for collective action by economic actors. However, in an industry 4.0 context, it allows for improved conditions of detection, economic recovery, flexibility, among others. In this sense, artificial intelligence allows the redefinition of its theoretical foundations, improving the efficiency of the health system.